A conceptual framework for a neurophysiological basis of art therapy for PTSD - Malhotra, Bani; Jones, Laura C.; Spooner, Heather; Levy, Charles; Kaimal, Girija; Williamson, John B. (Frontiers in Human Neuroscience, 2024)
Post-traumatic stress disorder (PTSD) is a heterogeneous condition that affects many civilians and military service members. Lack of engagement, high dropout rate, and variable response to psychotherapy necessitates more compelling and accessible treatment options that are based on sound neuroscientific evidence-informed decision-making. Art therapy incorporates elements proven to be effective in psychotherapy, such as exposure, making it a potentially valuable treatment option. This conceptual paper aims to inform the neurophysiological rationale for the use of art therapy as a therapeutic approach for individuals with PTSD. A narrative synthesis was conducted using literature review of empirical research on the neurophysiological effects of art therapy, with supporting literature on neuroaesthetics and psychotherapies to identify art therapy factors most pertinent for PTSD. Findings were synthesized through a proposed framework based on the triple network model considering the network-based dysfunctions due to PTSD. Art therapy’s active components, such as concretization and metaphor, active art engagement, emotion processing and regulation, perspective taking and reframing, and therapeutic alliance, may improve symptoms of PTSD and prompt adaptive brain functioning. Given the scarcity of rigorous studies on art therapy’s effectiveness and mechanisms of alleviating PTSD symptoms, the suggested framework offers a neurophysiological rationale and a future research agenda to investigate the impact of art therapy as a therapeutic approach for individuals with PTSD.